Unwelcome Immigrants: The Labor Market Experiences of 1980 (Mariel) Cuban and Haitian Refugees in South Florida - Portes, Alejandro; Stepick, Alex (American Sociological Review, 1985)
Alejandro Portes, Alex Stepick, Unwelcome Immigrants: The Labor Market Experiences of 1980 (Mariel) Cuban and Haitian Refugees in South Florida, American Sociological Review, Vol. 50, No. 4 (Aug., 1985), pp. 493-514